Effectiveness of A Teacher-Made Instructional Module in Electrical Installation and Maintenance for Grade 10 Students - Pagayon, Manolito A. (Future Science / FSH-PH Publications, 2025)
This study aimed to develop and assess the effectiveness of a teacher-made instructional module in Electrical Installation and Maintenance for Grade 10 students. Using a descriptive-experimental research method, the study involved seventy (70) Grade 10 students from Gumaca National High School enrolled in EIM. The results showed that the respondents found the module very acceptable across several criteria: topics, learning objectives, content, activities, assessment, applicability, presentation, layout, and user-friendliness. A significant improvement was also observed between the pre-test and post-test scores after using the module, indicating its positive impact on students’ cognitive skills. However, no significant relationship was found between the module’s features and the respondents’ technical skills.